2021
DOI: 10.1097/dcr.0000000000002059
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-C-Reactive Protein Ratio Is the Most Sensitive Inflammation-Based Prognostic Score in Patients With Unresectable Metastatic Colorectal Cancer

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Okugawa et al recently reported that LCR was the marker to predict the prognosis of CRC and GC cases ( 14 ). Two recent studies found that LCR showed was the most accurate in predicting patient prognosis relative to those existing inflammatory scores like NLR, LMR, PLR, and CAR ( 14 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Okugawa et al recently reported that LCR was the marker to predict the prognosis of CRC and GC cases ( 14 ). Two recent studies found that LCR showed was the most accurate in predicting patient prognosis relative to those existing inflammatory scores like NLR, LMR, PLR, and CAR ( 14 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes inhibit tumor cell proliferation and metastasis by promoting an immune response to the tumor and high CRP levels reflect proliferation and metastasis of tumor cells in patients with advanced cancer, with interleukin levels that can lead to cachexia and malnutrition, resulting in slower clearance of anticancer drugs and increased toxicity associated with therapy (36). On the other hand, relevant studies following the 2019 COVID-19 outbreak suggest that the LCR is potentially a predictive marker for COVID-19 infection and clinical deterioration, and given this evidence, the LCR may also reflect a frail or compromised host state (37)(38)(39)(40).Therefore, increasing LCR may be an effective strategy to improve tumor prognosis in patients with unresectable metastatic colorectal cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Okugawa (20) et al showed that two peripheral blood parameters, lymphocyte count and C-reactive protein level, had the highest correlation with recurrence compared to other parameters, and low preoperative LCR was significantly associated with undifferentiated histology, advanced T-stage, lymph node metastasis, distant metastasis, and advanced grade; reduced preoperative LCR was an independent prognostic factor for disease-free and overall survival, and was an independent risk factor for postoperative complications and surgical site infections in colorectal cancer patients; Wenting Ou (25) et al showed that LCR had the highest prognostic predictive value of all inflammatory scores and that low LCR was significantly associated with multiple clinicopathological features of tumor infiltration and progression. Nakamura (26) et al showed in a study of patients with unresectable metastatic colorectal cancer that the lymphocyte-c-reactive protein ratio was the most sensitive predictor of sustained survival among all prognostic scores based on inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations